Role of genetics and lifestyle in dysmenorrhea: Systematic Review (2023)
The aim of this systematic review was to identify the current state of knowledge on the association between susceptibility genes associated with this disorder and the lifestyle of patients (including diet, habits and stress levels). It also highlighted the advances made in this field of study, from a constructive point of view, and pointed out the perspectives for research into this disorder. Dysmenorrhoea, as a primary and secondary disorder, is one of the main causes of partial or total disability in the life cycle of women, both in reproductive age and later. It is recognised as a painful and disabling disorder which, depending on the cultural context, may or may not be cured by medical care, physiotherapy and the use of pain-relieving drugs, from an unknown aetiology (primary dysmenorrhoea) or concomitantly to surgical intervention (secondary dysmenorrhoea). Lifestyle, habits and diet have been identified as related to the intensity of pain and the disability it causes (active or passive use of cigarettes, consumption of alcohol, etc.), and genes related to the interpretation of pain generated by the patient from the morphology of the hypothalamus and the associative function of pain (BNDF Val66Met polymorphism) have been identified, as well as alterations in cytokines (in primary dysmenorrhoea), prostaglandins and an influence of the Cyp1A1 gene (in passive smokers). The study perspective is usually non-integrative and limited to the site studied, as well as to professional, laboratory, imaging (gynaecological and genetic) and/or molecular resources, which can only in a few cases be of an integral approach. Limitations are compounded by the fact that not all the populations studied are usually educated about menstruation, which also limits compatibility and comparability among studies.